2017
DOI: 10.1159/000485093
|View full text |Cite
|
Sign up to set email alerts
|

Huaier Extract Inhibits Breast Cancer Progression Through a LncRNA-H19/MiR-675-5p Pathway

Abstract: Background/Aims: Increasing evidence indicates that Huaier extract has promising therapeutic effects against cancer. However, the mechanisms that underlie its anti-tumor effects remain unclear. In recent years, various studies have shown that long noncoding RNAs (lncRNAs) play a critical role in the regulation of cancer development and progression. Here, we explored the role of lncRNAs in Huaier-induced tumor suppression. Methods: Microarray profiling was performed to identify the candidate lncRNAs affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 60 publications
3
44
0
Order By: Relevance
“…LncRNAs have been found to function as competing endogenous RNAs where they sponge miRNAs and regulate miRNA targets [16]. Wang et al found that Huaier extract inhibited BRCA through lncRNA-H19/miR-675-5p [17]. In the present study, the dysregulated expression of the lncRNA KCNQ1OT1 was found to be significantly associated with BRCA progression.…”
Section: Introductionsupporting
confidence: 57%
“…LncRNAs have been found to function as competing endogenous RNAs where they sponge miRNAs and regulate miRNA targets [16]. Wang et al found that Huaier extract inhibited BRCA through lncRNA-H19/miR-675-5p [17]. In the present study, the dysregulated expression of the lncRNA KCNQ1OT1 was found to be significantly associated with BRCA progression.…”
Section: Introductionsupporting
confidence: 57%
“…Considerable studies verified that lncRNAs exert their effects on diverse cancers, such as lung cancer, esophageal squamous cell carcinoma, and breast cancer (Seiler et al, 2017;Wang, Wang, Chen, Jiang, & Yang, 2017;Wu et al, 2017). As a new found lncRNA, MAGI2-AS3 has not been extensively reported in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, abnormal expression of lncRNAs contributes to the development and progression of cancer by influencing proliferation, apoptosis, autophagy, metastasis, self-renewal, and survival via epigenetic, transcriptional, and post-transcriptional gene regulatory mechanisms [10][11][12]. Furthermore, aberrant expression of lncRNAs can be detected in circulating cancer cells and in the serum and urine of cancer patients, which suggests that lncRNAs may serve as an effective biomarker for cancer detection and prognosis [13,14].…”
Section: Introductionmentioning
confidence: 99%